Uncovering Pathways Regulating ILC Metastasis Through miRNA Expression Analysis and Generation of Novel Invasive ILC Models - Allen, Victoria (Université d'Ottawa / University of Ottawa, 2019)
Invasive lobular carcinoma (ILC) is the second most common form of breast cancer. ILC presents at later stages with many challenges, therefore improved diagnostic and therapeutic targets are needed. A microRNA (miRNA) genome analysis identified miR-23c and miR-23b-3p as possible regulators of ILC invasion due to their significantly increased expression in invasive compared to minimally invasive ILC cell lines. By decreasing the levels of miR-23c and miR-23b-3p using hairpin inhibitors, the invasive MDA-MB-330 cell line had significantly reduced invasion, while overexpressing these miRNAs using mimics in the minimally invasive MDA-MB-134VI cell line increased invasion. During the course of this study, it became apparent that limited tools exist for studying invasive ILC. Therefore, two more invasive ILC cell line models were created by isolating and expanding MDA-MB-134VI cells that had invaded through Matrigel® coated invasion chambers. This thesis has thus created new models of invasive ILC as well as identified miR-23c and miR-23b-3p as regulators of MDA-MB-330 and MDA-MB-134VI cell line invasion.
Keywords: Invasive Lobular Carcinoma; miRNA; Invasion; Metastasis; Breast Cancer